Effect of shewing stimulus and acute stress on interleukin 6, memory and spatial learning in Balb/c mice - Aguirre-Siancas, Elias Ernesto (2023)
Introduction. Acute stress alters memory and spatial learning and the expression of interleukin 6, the chewing stimulus would prevent these effects. Objective. To determine the effect of chewing stimulation and acute stress on the expression of interleukin 6 and memory and spatial learning in mice. Methods. Experiment where 70 male albino mice of the Balb/c of age 2 month were randomly distributed into: Group A1: acute stress 1 hour; Group A2: acute stress 1 hour + chewing stimulus 1 hour; Group B1: acute stress 2 hours; Group B2: acute stress 2 hours + chewing stimulus 2 hours; Group C1: acute stress 3 hours; C2: acute stress 3 hours + chewing stimulus 3 hours; Group D: without intervention. For 3 days, spatial memory and learning were tested in the Morris water maze. Interleukin 6 (IL-6) was analyzed by ELISA test. Results. IL-6 was higher in the B2 group vs the other groups (p<0.0001). In addition, on the first day of evaluation, the acquisition of spatial memory and spatial was lower in the A1 vs. A2 group (p=0.042). Conclusión. Only on the first day of evaluation, we found that the masticatory stimulus prevented the decrease in memory acquisition and spatial learning in mice subjected to low-intensity acute stress. The results were generally inconclusive on the effect of masticatory stimulation. In addition, IL-6 was higher in the stress + masticatory stimulus (group B2) over the rest.